Quality of the systematic reviews in cochrane multiple sclerosis related articles - Masoud Zeynalzadeh; Nasim Mahdavi; Morteza Atayi; Hanieh Salehi-Pourmehr; Sakineh Hajebrahimi (BioSocial Health Journal)
Introduction: To enhance the assessment of the systematic reviews and meta-analyses performed by the Cochrane Multiple Sclerosis (MS) Group. Methods: Our study was conducted on 57 systematic reviews and meta-analyses related to MS, published by the Cochrane database until July 2023. Results: We found that the most encountered risk of bias was the low-risk domain, associated with Selective Reporting (data reporting), and followed by an unclear outcome for Allocation Concealment (selection bias). In contrast, Blinding of Participants and Personnel (performance bias) showed the highest risk of bias. Also, we concluded that up to 2015, the most prevalent risk of bias was ‘low outcome’ for Selective Reporting (data reporting). However, from 2016 till 2023, the most common risk of bias shifted to ‘low outcome’ for Random Sequence Generation (selection bias). Conclusion: Despite significant enhancements in improving the quality of studies, there is still a far way to achieve the ideal quality.